Borderline Personality Disorder and Mood Disorders: Mentalizing as a Framework for Integrated Treatment. Issue 8 (17th July 2015) - Bateman, Anthony; Fonagy, Peter; McMain, Shelley F.
<x xml:space="preserve">Abstract</x> Borderline personality disorder (BPD) frequently co‐occurs with mood disorders and each influences the course and response to treatment of the other, potentially reducing beneficial outcome. Mentalizing, the ability to infer one's own and others' mental states, is a key factor in both disorders, being a major component of affect regulation and self‐identity as well as a central aspect of interpersonal relationships and social function. In this article, we suggest that using mentalization‐based treatment may lead to better outcome by addressing the mentalizing problems arising from the dual pathway that leads from depressed mood and BPD to disruption of mentalizing. Some clinical interventions are described to address the mentalizing problems associated with depression and BPD.